(untitled) (Journal of Parents and Teachers, 2024)
It addresses violence in society and its impact on the educational environment, highlighting the need to create a safe environment for students. Various initiatives, such as awareness-raising days and contests, are proposed to encourage reflection and dialogue on violence. These activities seek to involve the educational community in the prevention of violence and promote a culture of peace and respect.